Studying human resource management : a guide to the study, context and practice of HR - Taylor, Stephen, 1965-; Woodhams, Carol (CIPD : KoganPage, 2022)
"Studying Human Resource Management is an ideal textbook for anyone studying the CIPD Level 5 Associate Diploma in People Management. Fully updated throughout, this book provides thorough coverage of the study of HRM, managing and co-ordinating the HR function, organisational performance and culture in practice as well as business issues in the context of HR. Written by experts in the field with both academic and practitioner experience, Studying Human Resource Management includes invaluable discussion on professional behaviours for people professionals and guidance on how to manage HR data and information and most importantly, how to use it to make evidence-based decisions. There are also now two brand new chapters on diversity and inclusion (D&I) and wellbeing at work. Each chapter includes key learning outcomes to summarise the content that will be covered and to help students track their progress, reflective activities to consolidate learning and further reading suggestions to support wider engagement with areas of particular interest. This book also includes case studies to help students understand how the theory applies in practice. Online resources include Powerpoint slides, a lecturer guide and annotated web links"--